Economic assessment of sustainable management approaches and technologies in agriculture: A systematic literature review - Hettiarachchi, Upeksha; Zhang, Wei; Suh, Neville; Lan, Grace (CGIAR System Organization, 2025)
The agricultural sector faces multiple sustainability challenges while meeting the rising food and nutrition demands of the global population. These challenges include biodiversity loss, land degradation, resource depletion, and disruptions of nutrient cycles caused by the very farming systems that feed us, thereby compromising food production for future generation. Agricultural activities contribute nearly 30 – 35% of GHG emissions, mainly due to livestock farming, deforestation, rice farming, and direct emissions from fertilized soils. Additionally, estimates show that irrigation and livestock farming contributes nearly 70% of freshwater withdrawals. With a rising global population, climate risks, rising cost of energy, and changes in people’s diet preferences, it is estimated that by 2050, approximately 70% more food must be produced sustainably to meet food security goals. Against this backdrop, a transition to sustainable agricultural farming systems is urgently needed to ensure global food security and environmental sustainability.